A racionalização das condições de trabalho nos hospitais: uma análise crítica baseada em relatos de ginecologistas obstetras e pediatras atuantes na urgência e emergência - Fachini, Flávia Granzotto (2016)
Hospitals are a big part of the service sector. Thus, such institutions are highly influenced by the logic of the capitalist accumulation, technology and forms of labor organization, especially by private organizations. Starting with the restructuring process motion and incorporation of technologies, many changes in the working process occur, therefore, the activities of medical professionals as well. During the preparation of this research items regarding the banalization of evil were identified. This banalization and resignation of the professionals face to violence are caused by the adoption of collective defense strategies. Therefore, this research aims to analyze how the rationalization of working conditions by gynecologists obstetricians and pediatricians working in the emergency rooms of public and private hospitals in Curitiba and metropolitan region occurs. An approach of mixed methods was used as methodological procedures. The naturalization of violence, the suffering which professionals are submitted to, are combined with the political and ideological control, bureaucratic control, the imaginary built about hospitals and collective defense strategies. It is therefore possible to understand that labor conditions of gynecologists obstetricians and pediatricians in emergency rooms are rationalized. When social injustice is naturalized, political strategies for changes are not possible. For this reason, the first step is to gather awareness, there is a need to unveil the reality, to understand the phenomena at its core and discard superficialities. It is also necessary that the actions and expressions of indignation to come hand in hand with political actions in order to change to happen.